Ambient RF energy harvesting system: a review on integrated circuit design - Chong, Gabriel; Ramiah, Harikrishnan; Yin, Jun; Rajendran, Jagadheswaran; Wong, Wei Ru; Mak, Pui-In; Martins, Rui P. (Springer, 2018)
This paper presents a comprehensive review of ambient RF energy harvester circuitry working on integrated circuits. The review covers 3 main blocks in an RF energy harvesting system implemented on chip. The blocks are the rectifier, impedance matching circuit and power management unit. The review of each block includes its operational principle, reported state-of-the-art circuit enhancement techniques, and design trade-offs. We compare the circuits in each block with respect to the techniques adopted to improve the performances for RF energy harvesting. To identify the benefits and limitations associated with the architecture we discuss the advantages and disadvantages of the circuit topologies in each block of an ambient RF energy harvester.